Promoting innovations in SMEs - findings from Kenya - Mugwika, Gatobu Rintaugu (Meru: Meru University of Science and Technology, 2022)
This paper looks closely at the relationship existing between entrepreneurial activity, innovations and the development of Small and Medium Sized Enterprises (SMEs). Most SMEs result from implementing the entrepreneurial spirit, through which the entrepreneurs$1 (Bactivity which is conducted in different domains. One of the most important aspect is the innovation in SMEs as an indicator of the entrepreneurial activity, on the one hand and as a contributor to the organization$1 (Bs performance, on the other hand. This study therefore analyses the SMEs innovation activity over a period of time as an indication of entrepreneurship evolvement and manifested in Kenya as an East African country that integrated relatively recently into the East African Community Common market (EAC). The paper envisages looking at how innovations in SMEs from Kenya have evolved in the period 2010 to date. The innovative activities in SMEs are examined from a dynamic perspective and the analysis is based on the study of a number of aspects related to innovations, such as: types of innovative activities, investments in innovations, the intensity of renewing the existing products, the use of IT, the use of the Internet, etc. Based on these findings, the paper attempts to characterize the innovative activities in Kenyan SMEs and their evolution in time with emphasis on the recent times.s